2014
DOI: 10.1096/fasebj.28.1_supplement.663.10
|View full text |Cite
|
Sign up to set email alerts
|

CHAC1 degrades glutathione, sensitizing cells to oxidative injury (663.10)

Abstract: CHAC1 is a pro‐apoptotic member of the endoplasmic reticulum stress pathway. The yeast homologue (YER163c) is the first known cytosolic protein to actively degrade glutathione (GSH), the most abundant antioxidant in the cell. However, the enzymatic activity of CHAC1 has not been fully characterized in mammalian cells. Herein, we investigate the effects of modulating CHAC1 in vitro on levels of cellular GSH and components of the GSH metabolic pathway in mammalian cells. Additionally, we define a role for CHAC1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Importantly, ABCC1 can export both GSH and various oxidized glutathione derivatives (e.g., glutathione disulfide (GSSG)), although with distinct substrate affinity [103][104][105]. Therefore, in addition to cellular enzymes that can degrade GSH (e.g., CHAC1 [106,107]) or regenerate GSH from GSSG (e.g., GSH reductase [108]), ABCC1 likely plays an integral role in maintaining the redox equilibrium in PSCs. It has been shown that oxidative stress downregulates key PSC-specific transcription factors OCT4 and SOX2, and compromises AKT signaling [97].…”
Section: Redox Regulation and Oxidative Stress (Abcc1 And Abcc4)mentioning
confidence: 99%
“…Importantly, ABCC1 can export both GSH and various oxidized glutathione derivatives (e.g., glutathione disulfide (GSSG)), although with distinct substrate affinity [103][104][105]. Therefore, in addition to cellular enzymes that can degrade GSH (e.g., CHAC1 [106,107]) or regenerate GSH from GSSG (e.g., GSH reductase [108]), ABCC1 likely plays an integral role in maintaining the redox equilibrium in PSCs. It has been shown that oxidative stress downregulates key PSC-specific transcription factors OCT4 and SOX2, and compromises AKT signaling [97].…”
Section: Redox Regulation and Oxidative Stress (Abcc1 And Abcc4)mentioning
confidence: 99%